Clinical significance of coefficient of variation in continuous glucose monitoring for glycemic management in children and adolescents with type 1 diabetes - Tatsuhiko Urakami; Hiroki Terada; Satomi Tanabe; Yusuke Mine; Masako Aoki; Ryoji Aoki; Junichi Suzuki; Ichiro Morioka (Journal of Diabetes Investigation, 2024)
Abstract Aims/Introduction Coefficient of variation (CV) is an indicator for glucose variability in continuous glucose monitoring (CGM), and the target threshold of %CV in type 1 diabetes is proposed to be ≤36%. This study aimed to evaluate the clinical significance of CV in children and adolescents with type 1 diabetes. Materials and Methods Participants included 66 children with type 1 diabetes. A total of 48 participants were treated with multiple daily injections of insulin, and 18 with continues subcutaneous insulin infusion, using intermittently scanned CGM. The frequencies of the CGM metrics and glycosylated hemoglobin values were examined, and the significance of a threshold %CV of 36% was evaluated. Results The mean frequencies in time in range (TIR), time below range, %CV and the mean glycosylated hemoglobin value were 59.3 ± 16.1, 4.0 ± 3.5, 39.3 ± 6.2 and 7.3 ± 0.8%, respectively. The frequencies of participants who achieved a TIR >70% and a %CV of ≤36% were 24.1 and 27.3%, respectively. A total of 18 participants with a %CV of ≤36% had significantly higher TIR, lower time below range and lower glycosylated hemoglobin than the 48 with a %CV of >36% (72.6 ± 12.6 vs 52.4 ± 13.6, 2.4 ± 1.9 vs 4.6 ± 3.6, 6.9 ± 0.8 vs 7.4 ± 0.7%, respectively). Conclusions Children and adolescents with type 1 diabetes using intermittently scanned CGM had difficulties in achieving the recommended targets of TIR and CV. However, the target %CV of ≤36% seems to be an appropriate indicator for assessing glycemic control and risk of hypoglycemia in pediatric patients with type 1 diabetes with any treatment.